Pengaruh etika kerja dalam Islam ke atas komitmen organisasi: Kajian dalam kalangan pihak berkuasa tempatan - Rahayu, Muhamad Yusuf (2013)
The main purpose of this study is to examine whether there is a relationship between islamic work ethic and organization commitment as well as to examine whether there is influence between islamic work ethic toward organization commitment. A total of 159 respondents were involved in this study consisting workers or staffs from Kulim Municipal Council, Kedah. Since this is a quantitative study, the researcher was used a statistic data as the main medium of the study. For the purpose of data collection, the researcher have used a set of questionnaire which divided into three sections. Section A focuses on the respondent personal details and followed by section B which involves some instruments about Islamic work ethic. Under the section C, the instrument involves related to the organization commitment. In order to analyze the data, researcher have been using the Statistic Package for Social Science (SPSS) of 16.0 version for the analysis purposes included process for entering data. The analysis used in this study involves frequency, descriptive analysis, Pearson correlation and simple regression with a purpose to examine the extent of relationship between islamic work ethic and organization commitment. The result obtain have supported the study objectives and directly proving that, there is a significant relationship between islamic work ethic and organization commitment as well as positively influence islamic work ethic toward organization among Kulim Municipal Council, Kedah staffs. Furthermore, limitations and suggestions for future study also provided by researcher